ISLAMIC BANKING EFFICIENCY AND INCLUSIVE SUSTAINABLE GROWTH: THE ROLE OF FINANCIAL INCLUSION - Hasanul Banna; Md Rabiul Alam (Journal of Islamic Monetary Economics and Finance, 2020)
This paper aims to estimate the efficiency scores of 153 Islamic banks of 32 countries during the period 2011 to 2017 by deploying data envelopment analysis and Simar–Wilson double bootstrapping regression techniques to determine how financial inclusion and its interaction effect with GDP growth impact on Islamic banking efficiency to promote inclusive sustainable growth. The findings show that the efficiency trends of Islamic banks in most countries have been inconsistent in the aftermath of the global financial crisis; this indicates that the banking industry is still bearing the consequences of that recession. However, Islamic banks in Bangladesh, Malaysia, Mauritia, Qatar, Tunisia, and Sudan are performing efficiently and, in spite of being war-affected countries, Islamic banks in Iraq and Palestine, more interestingly, have also seen an ascending trend in terms of improving their efficiency levels. The results foreground that to improve Islamic banks’ efficiency, financial inclusion (FI) must play a key role. Moreover, the effect of the interaction between FI and GDP growth suggests that FI plays a significant role in sustainable development, which creates a positive relationship between inclusive sustainable growth and the efficiency of Islamic banks. Since research on FI is an ongoing process, this paper contributes to the existing literature and methodology pertinent to the subject by analysing both non-bias and bias-corrected efficiency through the utilisation of more recent data from Islamic banks.